ANALISIS HUBUNGAN POTENSI RESAPAN AIR DENGAN POTENSI KEKERINGAN PADA DAS BATANG ARAU - Lutfi - Darwin; Ernawati Ernawati (DEPARTEMEN GEOGRAFI FIS UNP, 2022)
Some areas in Padang city experienced drought in September 2019. Based on BMKG data in that month the lowest rainfall (85.2 mm/mo) during 2019. BPBD mentions drought-affected areas, namely South Padang District and Lubuk Kilangan Subdistrict. The area is within the scope of Bt. Arau watershed. The purpose of this study is to find out the distribution area of potential water infiltration, the area of distribution of potential drought and its relationship. In determining the potential of water infiltration using parameters of soil type, rainfall, slope slope and land use. While the potential drought utilizes Landsat 8 Image for NDVI Transformation, Brightness, Wetness Index and its fisiographic influence. The methods used are overlay and scoring. As well as relationship determination using the Pearson Product Moment method in the R programming language. The results of this study obtained water infiltration conditions in the Bt. Arau watershed dominant in good condition with an area of 9788.7 Ha (56%) of the total area. While the potential for drought is in a rather high class of 10193.3 Ha (58.6%) of the total area. The results of the correlation test showed a correlated significance (having a relationship). As well as the correlation coefficient -0.31 means having sufficient relationship criteria and the direction of the relationship is reversed. This result can be used as a first step in drought mitigation in Bt. Arau watershed. Keywords—Bt. Arau watershed, GIS, Remote Sensing, R, Water Infiltration, Drought